Genetic dissection of new genotypes of drumstick tree (Moringa oleifera Lam.) using random amplified polymorphic DNA marker - Rufai, Shamsuddeen; Musa, Mohamed Hanafi; Yusop, Mohd Rafii; Selamat, Ahmad; Arolu, Ibrahim Wasiu; Ferdous, Jannatul (Hindawi Publishing Corporation, 2013)
The knowledge of genetic diversity of tree crop is very important for breeding and improvement program for the purpose of improving the yield and quality of its produce. Genetic diversity study and analysis of genetic relationship among 20 Moringa oleifera were carried out with the aid of twelve primers from, random amplified polymorphic DNA marker. The seeds of twenty M. oleifera genotypes from various origins were collected and germinated and raised in nursery before transplanting to the field at University Agricultural Park (TPU). Genetic diversity parameter, such as Shannon's information index and expected heterozygosity, revealed the presence of high genetic divergence with value of 1.80 and 0.13 for Malaysian population and 0.30 and 0.19 for the international population, respectively. Mean of Nei's gene diversity index for the two populations was estimated to be 0.20. In addition, a dendrogram constructed, using UPGMA cluster analysis based on Nei's genetic distance, grouped the twenty M. oleifera into five distinct clusters. The study revealed a great extent of variation which is essential for successful breeding and improvement program. From this study, M. oleifera genotypes of wide genetic origin, such as T-01, T-06, M-01, and M-02, are recommended to be used as parent in future breeding program.